Kebebasan Berbicara di Media Sosial: Antara Regulasi dan Ekspresi - Jam’ul Ihsan Bambang; Nadhratun Najwa; Muhammad Risky Rahmadani; Haya Salsabil; Arie Sulistyoko; Mufti Wardani; Ahmad Muhajir (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Social media has become an essential component of modern democracy, providing a platform for freedom of speech and public participation. Platforms like Facebook, Twitter, and Instagram allow people to freely express their opinions and engage in broad political discussions. However, challenges arise in the form of hate speech, hoaxes, and disinformation, which threaten social stability and the quality of democracy. This study aims to analyze the relationship between freedom of speech and democracy in the social media era and evaluate the regulations governing free speech in Indonesia. Using a normative approach, this research examines policies and regulations and their impact on human rights. The findings show that a balance between freedom of speech and prudent regulation is necessary to ensure that social media remains a positive space without sacrificing public order and democracy.